Modern Javanese Canned Gudeg Viewed from Cultural, Food Safety, and Visual Design Perspectives - Utami, Maya Putri; Maulana, Anand Reyna; Dukut, Ekawati Marhaenny; Wulandari, Dyah (Soegijapranata Catholic University, 2022)
Gudeg, a traditional culinary dish from Yogyakarta, Indonesia, is prepared by cooking young jackfruit with coconut milk and spices. It is commonly served with rice, eggs, chicken, and sambal goreng krecek, which is a spicy blended chili cooked with savory edible soft cowhide. Gudeg is interesting to discuss as it holds a rich history and is a cultural legacy that has been passed down through generations in Indonesia. Over time, gudeg producers have introduced an innovation of providing a visually attractive label on canned packages. This gives reason for research on gudeg using a cultural, food safety, and visual design perspective. The research found that culturally gudeg was the staple for the Mataram Kingdom army to survive the battle against enemies who wanted to colonialize the area. Next, the food safety test revealed that canned Gudeg Bagong had a microbial count of 1.3 x 10-1 CFU/ml, while canned Gudeg Andrawina Loka had a count of 2.4 x 10-2 CFU/ml. The findings demonstrated that the microbiological analysis met the standards set by Ministry of Health Regulation No. 416/MENKES/PER/IX/1990 and Indonesian Food and Drug Authority Regulation No. HK.00.06.1.S2.4011. Lastly, through visual design research, it was found among others that local and foreign tourists prefer to see the actual photo display of gudeg set with its jackfruit, egg, chicken, and sambal goreng krecek contents.